2013
DOI: 10.1038/sc.2012.167
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of oral health after spinal cord injury

Abstract: Study design: Cross-sectional study. Objectives: To examine predictors of oral health in people with spinal cord injury (SCI). Methods: Ninety-two people with SCI (X6 months, 44% cervical level) completed questionnaires and underwent oral examination. Socio-economic, injury-related and oral habits variables were used for predicting Oral Health Score (OHS); Decayed, Missing and Filled Teeth (DMFT) score; and Periodontal Screen and Recording Index (PSR). Results: Most people with SCI were able to bring at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Thus, it was a compromise between the patient's wish and the implementation of oral hygiene measures. 27 Dependency on caregivers for daily oral care may be an important determinant of oral health; dependent persons with SCI tend to have poorer oral hygiene, have more plaque, and more commonly have severe gingivitis and periodontal disease than independent persons. 28,29 Figure 3 indicated that the patient still has a lot of plaque in the anterior area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it was a compromise between the patient's wish and the implementation of oral hygiene measures. 27 Dependency on caregivers for daily oral care may be an important determinant of oral health; dependent persons with SCI tend to have poorer oral hygiene, have more plaque, and more commonly have severe gingivitis and periodontal disease than independent persons. 28,29 Figure 3 indicated that the patient still has a lot of plaque in the anterior area.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the caregivers were instructed regarding the oral hygiene measures the outcome needed improvement. 27 Furthermore, the medications necessary to reduce muscle tone and the frequency of muscle spasms or neurogenic bladder disorders in individuals with SCI can cause an increased accumulation of dental plaque and dental caries because of xerostomia. 30 Resulting dental diseases can not only cause physical and functional complaints but also lead to negative effects in the social, psychological and economic sectors.…”
Section: Discussionmentioning
confidence: 99%